Woodchip impregnation with weak white liquor and its effect in mitigating operational costs and environmental impacts in Kraft pulp mills. (7th May 2021) - Johakimu, Jonas K.; Sithole, Bruce B.
Abstract: Woodchip impregnation plays a vital role in enhancing Kraft pulp mill's pulping efficiency. Traditionally, Kraft pulp mills uses the mill's self‐generated liquor such as black liquor, green liquor, and white liquor. However, all these liquors have operational and / or pulping efficiency limitations. In this study, the feasibility of using weak white liquor as an alternative source of mill's self‐generated alkaline liquor for impregnating woodchips was investigated. South African Eucalyptus grandis woodchips were impregnated with and without weak white liquor. Under optimal conditions, the results showed that woodchips impregnated with weak white liquor responded much faster than the non‐impregnated ones (control). To maintain the same pulp and paper properties as the control pulp samples, a 20% reduction in the amount of cooking liquor used is required. When the experimental data were used to ascertain the economic and environmental benefits at an industrial mill scale, the savings in steam demand in the digester plant were estimated to be 23%. Energy savings in the lime kiln would be about 124 000 GJ per year. The reduction in carbon dioxide emissions in the calcination process was about 20%. Kraft pulp mills can use the information acquired in this study to determine whether this concept can be implemented in their commercial process. © 2021 Society of Chemical Industry and John Wiley & Sons, Ltd